Motion perception in touch: resolving contradictory findings by varying probabilities of different trial types. - Merz, S; Frings, C; Spence, C (Springer Nature, 2023)
Representational momentum describes the typical overestimation of the final location of a moving stimulus in the direction of stimulus motion. While systematically observed in different sensory modalities, especially vision and audition, in touch, empirical findings indicate a mixed pattern of results, with some published studies suggesting the existence of the phenomenon, while others do not. In the present study, one possible moderating variable, the relative probabilities of different trial types, was explored in an attempt to resolve the seemingly contradictory findings in the literature. In some studies, only consistently moving target stimuli were presented and no representational momentum was observed, while other studies have included inconsistently moving target stimuli in the same experimental block, and observed representational momentum. Therefore, the present study was designed to systematically compare the localization of consistent target motion stimuli across two experimental blocks, for which either only consistent motion trials were presented, or else mixed with inconsistent target motion trials. The results indicate a strong influence of variations in the probability of different trial types on the occurrence of representational momentum. That is, representational momentum only occurred when both trial types (inconsistent and consistent target motion) were presented within one experimental block. The results are discussed in light of recent theoretical advancements in the literature, namely the speed prior account of motion perception.